2014
DOI: 10.1523/jneurosci.0185-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of Learning Relates to Intrinsic Connectivity between Hippocampus, Ventromedial Prefrontal Cortex, and Large-Scale Networks

Abstract: An important aspect of adaptive learning is the ability to flexibly use past experiences to guide new decisions. When facing a new decision, some people automatically leverage previously learned associations, while others do not. This variability in transfer of learning across individuals has been demonstrated repeatedly and has important implications for understanding adaptive behavior, yet the source of these individual differences remains poorly understood. In particular, it is unknown why such variability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
73
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(78 citation statements)
references
References 47 publications
(5 reference statements)
5
73
0
Order By: Relevance
“…Related literature on acquired equivalence(27,28) shows that humans can link together stimuli that never appear together but which similarly predict subsequently appearing stimuli. Our finding of transfer within rule-sets extends this type of association to stimuli within hierarchical task-sets, and explores the nature of the clustering link.…”
Section: Discussionmentioning
confidence: 99%
“…Related literature on acquired equivalence(27,28) shows that humans can link together stimuli that never appear together but which similarly predict subsequently appearing stimuli. Our finding of transfer within rule-sets extends this type of association to stimuli within hierarchical task-sets, and explores the nature of the clustering link.…”
Section: Discussionmentioning
confidence: 99%
“…Prior work (Gerraty et al, 2014) has shown individual differences in resting-state functional connectivity relating to memory integration processes that support generalization. In apparent contrast to the present findings, that study found that intrinsic (i.e., not taske-voked) HPC-MPFC functional connectivity was negatively correlated with behavioral evidence for memory integration (Gerraty et al, 2014). However, HPC and MPFC also showed opposite connectivity-performance relationships with the default mode network (DMN), with low HPC-DMN and high MPFC-DMN connectivity being associated with superior integration.…”
Section: Discussionmentioning
confidence: 99%
“…Similar processes influence reward-based decisions in which a stimulus (A) acquires value through its secondary association (B) with monetary reward (C) (Wimmer & Shohamy 2012). The degree to which A comes to be associated with C is determined also by its interaction with schema-related processes in the vmPFC and its intrinsic resting-state connectivity with the HPC (Gerraty et al 2014). Similar processes may underlie performance on tests of second-order conditioning in rats (Gilboa et al 2014) and transitive inference in rats and humans who are presented with overlapping stimulus pairs in which one member of the pair is rewarded (e.g., A > B, B > C, C > D) and participants must infer how it is related to the other items (Preston & Eichenbaum 2013).…”
Section: Breaking Down Borders and Conquering Domainsmentioning
confidence: 99%